Influence of level of supplemental alfalfa hay on the performance of beef cows grazing winter bluestem range - E.S. Vanzant; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1992)
One hundred thirteen pregnant Hereford x Angus cows were used to study the effect of increasing levels of supplemental alfalfa hay on performance when grazing winter bluestem range. Although no differences were observed in reproductive performance, increasing the amount supplemental alfalfa from approximately .5% up to 1.0% of body weight resulted in increased weight gain and reduced condition loss in cows and increased weaning weight in calves. However, time spent grazing was significantly decreased in those groups receiving larger amounts of supplemental alfalfa.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Protein supplementation; Alfalfa hay; Beef cows; Winter range